EXPOSURE TO INCARCERATION AND COGNITIVE FUNCTIONING IN MIDDLE AGED MEN. (11th November 2018) - Cox, R
Abstract: Although aging may create unique challenges for reentry, there is a paucity of research on this topic. This study seeks to fill this gap by investigating cognitive functioning among formerly incarcerated middle age men using the 1979 National Longitudinal Survey of Youth. By constructing a cognitive functioning scale based on the one developed for the Health and Retirement Survey, I find the formerly incarcerated have significantly lower cognitive functioning scores than the non-incarcerated. Similar to Langa et al. (2017), controlling for education levels decreases the difference in cognitive functioning scores between the incarcerated and non-incarcerated. Unlike Langa et al. (2017), education does not completely wipe away the significance in cognitive functioning scores between the formerly incarcerated and the non-incarcerated. Nevertheless, controlling for early measures of cognition (i.e., AFQT scores) does eliminate the significant difference between the two groups, suggesting that differences in cognitive functioning may be established earlier in life.